On (∈,∈∨qk)-Fuzzy Hyperideals in Ordered LA-Semihypergroups - Muhammad Azhar; Naveed Yaqoob; Muhammad Gulistan; Mohammed M. Khalaf (Discrete Dynamics in Nature and Society, 2018)
The concept of (∈,∈∨qk)-fuzzy hyperideal of an ordered LA-semihypergroup is introduced by the ordered fuzzy points, and related properties are investigated. We study the relations between different (∈,∈∨qk)-fuzzy hyperideal of an ordered LA-semihypergroup. Furthermore, we study some results on homomorphisms of (∈,∈∨qk)-fuzzy hyperideals.